Paws. 2, Mindy makes some space - Fairbairn, Nathan; Msassyk; Assarasakorn, Michele (New York : Razorbill, 2022)
Best friends Gabby, Priya, and Mindy's dog business PAWS is booming, but between her mom starting to date and a new classmate wanting to join PAWS, Mindy's having a hard time sharing her feeling with her friends.
Kirkus Starred, November 2022
3.3
3-6
GN400L
Keywords: Mothers and daughters -- Comic books, strips, etc; Mothers and daughters -- Juvenile fiction; Families -- Comic books, strips, etc; Families -- Juvenile fiction; Best friends -- Comic books, strips, etc; Best friends -- Juvenile fiction; Friendship -- Comic books, strips, etc; Friendship -- Juvenile fiction; Dogs -- Comic books, strips, etc; Dogs -- Juvenile fiction; Business -- Comic books, strips, etc; Business -- Juvenile fiction; Mothers and daughters -- Fiction; Family life -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Dogs -- Fiction; Graphic novels; Comics (Graphic works)